Situation-Based Security Learning Packages Design - He, Xingwei; Jongkonklang , Sirinat; Pilanthananond, Nataya (Academic MCU Buriram Journal, 2025)
This study focuses on the design of “Situation-Based Security Learning Packages” aimed at enhancing security education effectiveness through situational learning theory. Current challenges in security education for college students include varying levels of interest in security knowledge and a gap between theoretical understanding and practical application. The study aims to develop and implement situational security education packages to enhance students' knowledge, coping skills, and engagement in learning. The research commenced with a needs assessment and objective identification for security education among college students. Learning packages were designed based on situational learning theory, covering topics such as national, public, personal, property, fire, traffic, psychological, and laboratory security. Each topic includes sections on introduction, objectives, activities, resources, and evaluation modules. These are designed to simulate real security scenarios for experiential learning. The effectiveness of these learning packages was evaluated by seven experts who assessed the relevance of teaching topics, richness of resources, and practicality of activities. A preliminary experiment involving five college students demonstrated a significant increase in both enthusiasm for learning and awareness of security issues. The results indicate that these packages effectively enhance students' awareness of security issues, their ability to cope with security challenges, and their overall interest in learning. Future developments could expand the scope of content covered and integrate modern technologies such as virtual and augmented reality to further improve learning outcomes.